SERVICE QUALITY ON THE CUSTOMER SATISFACTION AT PEGADAIAN UPC ANDI TONRO DURING PANDEMIC COVID-19 - Siti Nurhaliza Azis; Muh. Ichwan Musa; Muhammad Ilham Wardhana Haeruddin (ADISAM Publisher, 2022)
This research aims to know Service Quality On The Customer Satisfaction at Pegadaian UPC Andi Tonro During Pandemic Covid-19. The sampling was determined insidental technique, the sample in this research was 100 respondents. The method data collection was observation, questionnaires and interview. The data analysis were, realibility, simple linear regression, and hypothesis testing. The results show that the service quality has a positive and significant impact on the Customer Satisfaction at Pegadaian UPC Andi Tonro During Pandemic Covid-19. Based on T value obtained 2,322>1,984 and significant value obtained 0,02<0,05 and the value of R square (R2) of 0,052 obtained 5,2%. The indicator of service quality with the most dominant influence is the indicator of tangible and assurance, while the indicator of customer satisfaction with the most overall customer satisfaction